PENGARUH TATA KELOLA PERUSAHAAN PENGARUH TATA KELOLA PERUSAHAAN DAN PERATAAN LABA TERHADAP KONSERVATIF AKUNTANSI - Siti Nur Hidayati; Slamet Haryono (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
Accounting conservatives can anticipate losses but not report finances. In this study, the indicators used to measure accounting conservatives are managerial ownership, institutional ownership, independent ownership, and income smoothing. The sample used was 7 companies and randomly selected which were registered in the LQ45 index for the period 2013 to 2019. Data were obtained from the publications of each company. The data analysis technique used is panel data regression analysis with the random effect selected model. The results of this study indicate that simultaneously managerial ownership, institutional ownership, independent ownership, and income smoothing variables have an effect on accounting conservatives. As for partially, managerial ownership, institutional ownership, and income smoothing variables affect accounting conservatives. The existence of the influence of these three variables to increase public confidence by implementing conservative accounting. while the independent ownership variable has no effect on accounting conservatives because individual share ownership does not affect accounting conservatives. Keywords: Accounting conservative, managerial ownership, institutional ownership, independent ownership, and income smoothing